Architectural solutions for collective housing for young people - Ogienko, Evgeny; Kolesnikov, Aleksander (project baikal, 2026)
Using examples of residential complexes from Japan, South Korea, the United States, Israel, Turkey, and the United Kingdom, this article examines the architectural, planning, and social aspects of youth housing. Particular attention is paid to shared living models that balance personal space with public areas, as well as the integration of amenities into the living environment. An analysis of projects in these countries demonstrates a trend toward creating adaptive, cost-effective, and socially oriented residential spaces tailored to the needs of the younger generation.
Keywords: youth housing; collective living; social housing; amenities; public spaces; residential complexes; adaptive spaces